Beneficial effects of linagliptin in cell culture model of Parkinson’s disease - Okkay, Ufuk; Ferah Okkay, Irmak (The European Research Journal, 2022)
Objectives: We aimed to investigate the neuroprotective effects of linagliptin in an in vitro 6-hydroxydopamine (6-OHDA) Parkinson’s disease model. Methods: 6-OHDA (200 µM) were administered to the SH-SY5Y cells for 24 h to induce Parkinson’s disease model in vitro. Cells were treated with linagliptin (1, 10, 50 and 100 nM) 30 minutes before 6-OHDA administration. Cell viability was examined by 3-[4,5-dimethylthiazole-2-yl]-2,5-diphenyltetrazolium bromide (MTT) method and lactate dehydrogenase (LDH) analysis. Superoxide dismutase (SOD), catalase (CAT), malondialdehyde (MDA) and reactive oxygen species (ROS) analyses were conducted to assess oxidative stress. Apoptosis was evaluated with Caspase-3 mRNA expression levels. Results: It was observed that 6-OHDA elevated LDH levels and cell death. Oxidative stress was exaggerated with increased ROS and MDA levels and substantially apoptosis was proven with increased Caspase-3 levels in SH-SY5Y cells. Pretreatment with linagliptin alleviated oxidative stress and apoptosis. Conclusions: Given its neuroprotective role as well as its effects on oxidative stress and apoptosis, linagliptin may be a drug candidate in Parkinson’s disease.